Eksplorasi Potensi Wisata Kuliner Untuk Pengembangan Pariwisata Di Kabupaten Simalungun - Mohammad Yusuf Dalimunthe (Politeknik Pariwisata Medan, 2023)
This study aims to explore the potential of culinary tourism as an effort to develop tourism in Simalungun Regency. Qualitative methods were used in this study to gain a deep understanding of local culinary potential, interactions between culinary entrepreneurs and tourists, and the role of culinary tourism in regional tourism development. The participatory observation method is carried out by participating directly in culinary activities at culinary tourism locations in Simalungun Regency. The observer observes culinary practices, social interactions, and the atmosphere at the culinary places that are the focus of the research. In addition, in-depth interviews were conducted with culinary business owners, local tourism experts, local communities, and tourists who have visited Simalungun Regency. This interview provides insight into their views, experiences and knowledge regarding the potential for culinary tourism and the role of tourism development. The collected data is analyzed using a thematic approach to identify patterns, themes, and issues that arise in exploring the potential for culinary tourism. The results and findings of this study will provide better insight into local culinary potential, challenges faced, and opportunities for tourism development in Simalungun Regency. This research is expected to contribute to the development of culinary tourism in Simalungun Regency. The findings and recommendations from this research can be the basis for developing sustainable culinary tourism development strategies and strengthening regional culinary identities.